Rising burden of cancer and atrial fibrillation–related mortality among adults in the United States, 1999–2019 - Muhammad Saad, MBBS; Reyan Hussain Shaikh, MBBS; Muhammad Umer Sohail, MBBS; Saad Ahmed Waqas, MBBS; Mian Muinuddin Jamshed, MBBS; Syed Ibad Ahsan, MBBS; Muhammad Sameer Arshad, MBBS; Azeem Hassan, MBBS; Sebastian Mactaggart, MBBS; Raheel Ahmed, MBBS, MRCP, PhD (Heart Rhythm O2)
Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia, whereas cancer remains the second leading cause of death in the United States. Both conditions share several risk factors and may compound mortality risk. However, national trends in AF and cancer-related mortality remain underexplored. Objective: To assess trends in mortality related to AF and cancer among US adults from 1999 to 2019, using demographic and geographic stratifications. Methods: Data were obtained from the CDC WONDER Multiple Cause of Death data set. We identified individuals aged 25 years and older with AF (I48) and cancer (C00-C97) as an underlying or contributing cause of death. Age-adjusted mortality rates (AAMRs) per 100,000 population, average annual percentage change, and annual percentage change were calculated. Results: The AAMR for cancer and AF-related deaths increased from 4.95 (95% confidence interval [CI]: 4.84, 5.05) in 1999 to 10.01 (95% CI: 9.88, 10.13) in 2019 (average annual percentage change: 3.49 [95% CI: 3.39, 3.60]). Males had higher AAMRs than females (10.24 vs 5.13). Non-Hispanic Whites had the highest AAMRs (7.89), followed by non-Hispanic Blacks (4.53) and Hispanics (3.11). The Western region had the highest AAMR, and nonmetropolitan areas exhibited greater mortality rates than metropolitan areas. Individuals with lung cancer exhibited the highest AAMRs (1.65), followed by gastrointestinal cancer (1.52) and hematologic cancer (1.00). The lowest AAMRs were observed in prostate cancer (0.90) and breast cancer (0.65). Conclusion: Mortality from cancer and AF has increased over time, with significant disparities across sex, race, and geography. Targeted interventions are required to mitigate these disparities.